Pendampingan Kompetensi Pendidik TPQ al Maghfiroh Dusun Pilangglenteng Gondang Nganjuk - Iswanto, Juni (LP3M STAI Darussalam Krempyang Nganjuk, 2019)
The teacher is one of the important components in the teaching and learning process that participates in the formation of potential human resources in the field of development. Therefore, the teacher must play an active role and place his position as a professional force, in accordance with the demands of a growing community. TPQ al-Maghfiroh is an Islamic educational institution located in the Pilangglenteng Hamlet of Karangsemi Village, Gondang District, Nganjuk Regency. Educators at TPQ have not mastered the full learning methods. The approach in this service uses the Asset-Based Community Development (ABCD) approach.